Autogenic incision‐backfilling cycles and lobe formation during the growth of alluvial fans with supercritical distributaries. Issue 6 (4th June 2013) - Hamilton, Paul B.; Strom, Kyle; Hoyal, David C. J. D.
Abstract Autogenic cycles of channelization, terminal deposit formation, channel backfilling and channel abandonment have been observed in the formation of fans and deltas. In subcritical flow, these terminal deposits are characterized as mouth bars that lead to flow bifurcation, backwater and eventual channel backfilling. Similar, although less well characterized, cycles also take place on supercritical subaerial and submarine fans. This study investigates the hydraulics and morphodynamics of autogenic incision and backfilling cycles associated with supercritical distributive channel flow in alluvial fans. The research questions of the study are: (i) how are supercritical autogenic cycles on alluvial fans different from the subcritical cycles; (ii) what are the hydraulic and sediment transport characteristics at the various stages of autogenic feedback cycles; and (iii) what role do the cycles play in the overall fan evolution? These questions are investigated in the laboratory, and emphasis is placed on measuring the hydraulic and topographic evolution of the systems during the cycles. The cycles arise quasi‐periodically under constant water and sediment discharge. Periods of sheet‐like flow are competent to move sediment (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3hzbk4vv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />τ*>τcr*</alternatives>) but not competent enough to carry the full imposed load. The net result is preferential deposition near the inlet, resulting in fan steepening and an increase in flow competency with time. At a sediment supply to capacity ratio of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3hzbk4wd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Qs/Qc≈0·75</alternatives>, the sheet‐like flow is unstable to small erosional events near the inlet, resulting in the collapse of the distributed flow to a strong channelized state. During channelization, a graded (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3hzbk50k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Qs/Qc≈1</alternatives>) supercritical (Fr > 1) channel develops and transports eroded and fed sediment up to and through the fan front – extending the fan, initiating a lobe shaped deposit and reducing the local slope. The slopes defined by a sheet‐like flow with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3hzbk514" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Qs/Qc≈0·75</alternatives> and channelized flow with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3hzbk4xz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Qs/Qc≈1</alternatives> set the maximum and minimum slopes on the fan, respectively. Once formed, graded channels act as bypass conduits linking the inlet with the terminal deposit. On average, deposits are up to six channel depths in thickness and have volumes approximately five times that of the excavated channel. The main distinctive characteristics of the supercritical cycles relate to how the flow interacts with the terminal deposit. At the channel to deposit transition, the flow undergoes a weak hydraulic jump, resulting in rapid sedimentation, dechannelization and lateral expansion of the flow, and deposition of any remaining sediment on top of the channel fill and floodplain. This process often caps the channel as the deposit propagates up channel erasing memory of the excavated channel.